Safety and effectiveness of a posterior approach alone for surgical treatment of sacral-presacral tumors - Demir, Fatih; Kaplan, Metin; Akgun, Bekir; Kok, Selman; Ozturk, Sait; Erol, Fatih (Wolters Kluwer Medknow Publications, 2023)
Aim: We aimed to examine the safety and effectiveness of a posterior approach alone in the surgical treatment of sacral-presacral tumors. In addition, we investigate factors that determine the selection of a posterior approach alone. Materials and Methods: Patients with sacral-presacral tumors who underwent surgery in our institution between 2007 and 2019 were examined in this study. Data regarding patient age, gender, tumor size (>6 cm and <6 cm), tumor localization (below or above S1), tumor pathology (benign or malignant), surgical approach (anterior alone, posterior alone, or combined), and extent of resection were recorded. The Spearman's correlation analyses were conducted between surgical approach and tumor size, localization, and pathology. Factors influencing the extent of resection were also examined. Results: Complete tumor resection was achieved in 18 of 20 patients. A posterior approach alone was used in 16. No strong or significant relation was detected between surgical approach and tumor size (r = 0.218; P = 0.355). There was no strong or significant relationship between surgical approach and tumor localization (r = 0.145; P = 0.541) or tumor pathology (r = 0.250; P = 0.288). Tumor size, localization, and pathology were not independent factors that determined surgical approach. The only significant independent determining factor for incomplete resection was tumor pathology (r = 0.688; P = 0.001). Conclusion: A posterior approach is safe and effective in the surgical treatment of sacral-presacral tumors independent of tumor localization, size, or pathology and is a feasible first-line treatment option.
Keywords: Posterior approach; sacral-presacral tumors; surgical management